The Estoppel Principle in Public International Law - Basim Abdulmajid, Assist .Lect . Sura (Basra studies journal, 2024)
The estoppel principle is one of the most important rules governing relations between states. According to this rule, a state is prohibited from acting in a way that contradicts its previous actions to the detriment of other states. This principle requires an international person to refrain from asserting anything that contradicts, denies, or opposes what it has previously accepted or agreed to, explicitly or implicitly, through words, actions, or conduct, which goes against the principle of good faith. The estoppel principle also serves as an appropriate corrective tool that helps achieve stability in relations between states, reinforces the requirements of ethics, and embodies justice among states.